Jurnal Pengaruh Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Pada Toko Rotte Bakery Di Bangkinang Kota : - - Sitohang, Zekry (Universitas Muhammadiyah Riau, 2024)
Rotte Bakery is one of the well-known bakeries in Bangkinang City, facing challenges in maintaining its position in an increasingly competitive market. With so many choices of bread and other bakery products, Rotte Bakery must maintain the quality of its products to remain the first choice for consumers. Apart from that, setting the right price is also important to attract more consumers without sacrificing company profits. This research aims to analyze the influence of product quality and price on purchasing decisions at Rotte Bakery Bangkinang City. This research uses quantitative methods with the Accidental Sampling technique. The research population was 39,085 people, and the sample used was 100 respondents. The research results show that either partially or simultaneously, product quality and price have a significant influence on purchasing decisions at Rotte Bakery.